Determining the impact of experiential marketing on consumer satisfaction: A case of India’s luxury cosmetic industry - Rati Dhillon (LLC "CPC "Business Perspectives", 2021)
The growth of consumerism in the luxury cosmetic industry in India is backed by the ability and willingness of the consumers to spend money, internet penetration, awareness, and consciousness of luxury cosmetics from exposure to beauty brands. Among other methods of marketing, the adoption of experiential marketing is gaining ground. It is specifically relevant in the cosmetic industry as it creates behavioral experience, brand experience, and brand engagement for appealing to the affective, sensory, and intellectual aspects of the consumers. The study examines the impact of experiential marketing on consumer satisfaction while identifying its importance in the industry. With the help of a close-ended questionnaire, a survey was conducted to examine the perception of 820 consumers of luxury cosmetics in India. SEM analysis was conducted to examine the impact of experiential marketing on consumer satisfaction using SPSS AMOS software. Herein, experiential marketing is represented by five components i.e. relate, feel, think, act, and sense while customer satisfaction by three components i.e. overall service quality, individual experience, and service quality, and perceived expectation-actual performance. The findings of the study revealed the presence of a positive impact.